Immobilized cell systems for batch and continuous winemaking - Genisheva, Zlatina Asenova (2014)
The major challenges in the food industry are the development of healthier, safer and environmental friendly products. To achieve these objectives, it is essential to develop advanced technologies to make the production processes economically attractive. The use of immobilized cell systems has been widely applied in the production of several products. However, in winemaking, it has only been studied to prove its applicability. The studies targeting the production of wine using these innovative fermentation systems aim to overcome limitations related to the product quality, the operational costs associated with the material used as support and the immobilization process itself.